Soft Power of the UAE: Dubai Cares Project in Uganda - Retno Amalia Ningrum; Muhammad Farid (Andalas Journal of International Studies (AJIS), 2024)
Uganda was one of the countries, which have received South Sudanese refugees since 2013. Since that period of time, South Sudanese refugee children in Uganda have faced challenges such as school dropouts, health issues, hunger, and family loss. Amid this crisis, the United Arab Emirates (UAE) intervened through Dubai Cares to support the rights of South Sudanese refugee children in Uganda through education program. The research employs a qualitative method by analyzing primary data from official government reports and websites, as well as secondary data from academic literature, reports, and online newspaper publications to examine the implementation of the Dubai Cares project for South Sudanese refugee children in Uganda. The concept of soft power is used to understand how the UAE leverages the Dubai Cares as a soft power instrument. Soft power concept serves to confirm that the UAE uses Dubai Cares to spread the country’s influence without resorting to coercive measures. The study finds that Dubai Cares enhances the UAE's attractiveness, reputation, and influence on the international stage through its educational programs for South Sudanese children in Uganda.